Sonocrystallization of a Tristearin‐Free Fat. (30th May 2018) - Kadamne, Jeta V.; Moore, Maria; Akoh, Casimir C.; Martini, Silvana
Abstract: The objective of this study was to fractionate a purified interesterified fat to eliminate tristearin (SSS) and to evaluate the crystallization behavior of the tristearin‐free fat. The fractionated sample was crystallized with and without the application of high‐intensity ultrasound (HIU) by supercooling the sample at 2 °C. In the absence of SSS, the crystallization process was driven by low‐melting‐point triacylglycerols (TAG) such as OSS and OOS (O, oleic; S, stearic acid). There were no differences observed in the crystallinity in the sample based on the solid fat content ( P > 0.05) along with any microstructural differences. In addition, an increase in the enthalpy of melting was observed upon sonication, indicating higher crystallinity ( P < 0.05). Stronger intramolecular forces were formed in the sonicated samples as evidenced by increased viscoelastic parameters such as the elastic modulus ( G ′) and storage modulus ( G ″) ( P < 0.05). G ′ values increased from 138.25 ± 41.30 to 939.73 ± 277.45 Pa while the G ″ values increased from 39.15 ± 8.98 to 149.77 ± 16.00 Pa ( P < 0.05). Change in viscosity was not observed as a consequence of sonication ( P > 0.05). This study showed that HIU was effective in changing the crystallization behavior of SSS‐free fats with low‐melting TAG.